ANALISIS FAKTOR-FAKTOR PENYEBAB ANAK PUTUS SEKOLAH - Fatimah, Nurul; Genjik, Bambang; Witarsa, Witarsa (Universitas Tanjungpura, 2023)
Dropping out of school is a serious problem that can hamper the country's social and economic development. Therefore, it is necessary to analyze the causal factors in order to overcome these problems. This article discusses the results of an analysis of the factors that cause children to drop out of school based on literature studies and primary data obtained from interviews with fathers/mothers of students and teachers in several schools. The results of the analysis show that factors such as economic, social, and personal can cause children to drop out of school. Economic factors include expensive school fees and unmet family financial needs, while social factors include an unsupportive family environment and social pressure in the school environment. Personal factors include lack of motivation and interest in learning as well as health and psychiatric problems. Therefore, integrated and collaborative efforts between the government, community and schools need to be made to address the problem of dropping out of school by taking into account these factors.